Does Static Intra Access Pressure Monitoring of Arteriovenous Fistulas Predicts Intra Access Stenosis? - Rehman, Abaid ur; Khan, Muhammad Imran; Sabir, Omer; Riaz, Muhammad Mohsin; Dilawar, Mubashar; Afzal, Hafiz Usman; Basit, Muhamad Bilal (Pakistan Journal of Kidney Diseases, 2021)
The initiation of hemodialysis in patients with chronic kidney disease (CKD) requires vascular access formation. The choice of vascular access for individual patient depends on various factors however arteriovenous fistula (AVF) is conventionally considered to be the vascular access of choice. Once hemodialysis is initiated through a mature AVF, there is an ongoing need for surveillance of the AVF to ensure adequate function and prevent vascular access issues among which flow obstruction (both inflow and outflow) remains the most important. AVF stenosis can potentially lead to inadequate dialysis delivery and thrombosis thus leading to access loss. Physical examination and AVF Doppler ultrasonography (DUS) are useful for evaluation of stenosis in the arteriovenous connection and the outflow tract. Periodic assessment of the AVF with Static Intra access Pressure (SIAPR) determination may be a reliable means of predicting vascular access stenosis. Material & Methods A cross sectional study carried out at Department of Nephrology, Fatima Memorial Hospital, Lahore from July 2018 to December 2018. In total 113 patients were included, and all patients underwent SIAPR assessment and Doppler Ultrasound of AVF. Results Mean age of the patients was 56.81±9.38 years, male to female ratio of the patients was 1.8:1. In this study the SIAPR was suggestive of stenosis in 87(76.99%) patients. The sensitivity, specificity and diagnostic accuracy of SIAPR against Doppler US of the AVF for detection of stenosis was 75.86%, 22.62% & 36.28% respectively Conclusion SIAPR has low specificity and diagnostic accuracy compared to Doppler US for detection of AVF stenosis.